2016
DOI: 10.1186/s40249-016-0187-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis care strategies and their economic consequences for patients: the missing link to end tuberculosis

Abstract: BackgroundWhile investment in the development of Tuberculosis (TB) treatment strategies is essential, it cannot be assumed that the strategies are affordable for TB patients living in countries with high economic constraints. This study aimed to determine the economic consequences of directly observed therapy for TB patients.MethodsA cross-sectional cost-of-illness analysis was conducted between September to November 2015 among 576 randomly selected adult TB patients who were on directly observed treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
3
35
2
5
Order By: Relevance
“…This study showed that the average OOP payment was USD 2389.5 for TB patients during the whole TB episode, which was equivalent to 27.4% of the annual household income. The proportion was higher than that in Pakistan (5.4%) [15] and lower than those in Ethiopia (152%) [21] and Nigeria (37%) [22]. Direct medical costs accounted for the majority of the costs in this population, inconsistent with other studies that showed a high proportion of non-medical costs and indirect costs [23,24].…”
Section: Interpretation Of Key Findings Oop Payments and Their Componcontrasting
confidence: 80%
“…This study showed that the average OOP payment was USD 2389.5 for TB patients during the whole TB episode, which was equivalent to 27.4% of the annual household income. The proportion was higher than that in Pakistan (5.4%) [15] and lower than those in Ethiopia (152%) [21] and Nigeria (37%) [22]. Direct medical costs accounted for the majority of the costs in this population, inconsistent with other studies that showed a high proportion of non-medical costs and indirect costs [23,24].…”
Section: Interpretation Of Key Findings Oop Payments and Their Componcontrasting
confidence: 80%
“…While most studies used the broad categories of strategies for coping with healthcare costs commonly covered in international household surveys (eg, using income/savings, borrowing money or selling assets) some drilled down to distinguish between types of borrowing and asset sales 19–28. For example, some studies examined who households borrowed from, noting that those forced to borrow from moneylenders faced higher interest rates than those borrowing from family or friends 25 26 28.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the lower recovery rate of TB and lowerlevel Medical insurance coverage are both lead to The long-term existence of the source of infection, which is similar to the results of recent studies. [37,38] The situation of failed TB treatment and out-of-pocket payments with catastrophic consequences will hamper the efforts to end TB.…”
Section: Discussionmentioning
confidence: 99%